Reception of sharia-compliant homestay accommodations in Sabah: Insights and implications - Suhailah Abdul Muin; Dzurizah Ibrahim; Norcikeyonn Samuni (Human Resource Management Academic Research Society (HRMARS), 2024)
The growing prominence of Sharia-compliant tourism in Sabah, Malaysia, presents both opportunities and challenges for the hospitality industry. Understanding tourists' perceptions and preferences for such accommodations is crucial for providing meaningful and compliant experiences. However, limited research has explored this emerging market segment and its impact on the tourism industry. This study aims to investigate tourists' reception of Shariacompliant homestay accommodations in Sabah. Specifically, it seeks to assess tourists' preferences and acceptance levels, and uncover potential implications for the tourism and hospitality sector. A quantitative research approach, utilizing a descriptive survey design, was employed. A sample of 260 participants, primarily domestic tourists, was selected through random sampling. Data was collected using structured questionnaires consisted of ten items measured on a 5-point Likert scale, covering various aspects of Sharia-compliant accommodations. Data analysis included descriptive statistics and the identification of trends and patterns. The study revealed a high level of acceptance and positive attitudes among tourists toward Sharia-compliant homestay accommodations in Sabah. Tourists prioritize such accommodations due to perceived benefits, safety, and comfort. They generally accept Islamic regulations and policies, provided they do not compromise privacy. However, willingness to pay extra for these services varied among respondents, highlighting the importance of competitive pricing strategies. While the study focused on domestic and Muslim tourists, the findings offer valuable insights into the potential demand for Shariacompliant homestays among a broader tourist population. The findings hold several implications for the tourism and hospitality sector in Sabah. They emphasize the importance of maintaining high service quality, including efficient management, cleanliness, halal dining, and prayer facilities, to attract and retain tourists. Additionally, the study suggests the need for diversified pricing strategies to cater to varying budget preferences within the market. This research serves as a foundation for further exploration of Sharia-compliant tourism and its potential contributions to Sabah's tourism industry, making it a valuable resource for policymakers, industry stakeholders, and researchers alike.